OPTIMIZATION OF TRANSPORT ACTIVITIES IN THE SUGAR BEET HARVESTING CAMPAIGN - Dejan Brcanov; Stojanka Dakić; Danilo Đokić; Nebojša Gvozdenović; Stanislav Zekić (Ekonomika Poljoprivrede (1979))
This paper explores the optimization of sugar beet transport from loading points to processing plants throughout the harvest campaign. An optimization model was developed to address the key logistical aspects of this process. The approach was applied to data from a company that encompasses 50% of Serbia’s sugar beet processing, with operations across three sugar factories. The results include an evaluation of the current operating method and the analysis of two alternative scenarios that present further opportunities to reduce logistical costs. These savings not only lower company expenses but also contribute to reduced greenhouse gas emissions, underscoring both economic and environmental benefits.